Increasing Listening Skill by Using Podcast - Ibnu Fiqri Ayatulla; Abdillah Surya Dirgantara Ginting (JELT : Journal of English Education, Teaching and Literature, 2024)
This research is a descriptive qualitative research with a strategic case study research strategy. This research was conducted at the AL-ITTIHADIYAH Senior High school. This research was conducted at AL-ITTIHADIYAH on how big the impact of podcasts is in improving students' listening skills. This research was conducted for two months starting in November to December 2023. Informants who are the source of data in this study are students of high school students at the same school. Secondary data in this study sourced from documents, including books, student assignments and researches.